A concept analysis and overview of outcome measures used for evaluating patients with proximal humerus fractures. Issue 10 (8th May 2021) - Nowak, Lauren L.; Davis, Aileen M.; Mamdani, Muhammad; Beaton, Dorcas; Schemitsch, Emil H.
Abstract: Purpose: It is unclear to which degree existing studies evaluate the primary goal of treatment for patients with proximal humerus fractures (restoration of daily activities). Our purpose was to systematically review and analyze the concepts reflected by outcome measures used in studies of patients with proximal humerus fractures. Methods: We reviewed three databases from 2000 to 2018. Two reviewers categorized outcomes in each study into concepts of the International Classification of Functioning, Disability and Health framework. Results: The most commonly represented concept across 35 studies was "Body Function/Structure Impairment", followed by aggregate measures that reflect multiple concepts to varying degrees. All patient-reported aggregate measures such as the Disabilities of the Arm, Shoulder, and Hand, American Shoulder and Elbow Surgeon's, and Oxford Shoulder scores better reflected "Activity Limitations", however, these measures were only reported in 34% of studies. Conclusion: There may be misalignment between what studies measure, and the primary goal of treatment for patients with proximal humerus fractures. The Disabilities of the Arm, Shoulder and Hand, American Shoulder and Elbow Surgeon's, and Oxford Shoulder scores reflect concepts that more adequately address the restoration of daily activities following these injuries, and future studies should include at least one of these measures. Implications for rehabilitation: We have shown that there is a misalignment between what existing studies are measuring (primarily objective measures of impairment) and the primary goal of treatment and rehabilitation (restoring activities of daily living). This suggests that existing studies evaluating different treatment types for proximal humerus fracture patients are providing inadequate information to make evidence-based treatment and rehabilitation decisions following theses injuries. Our results tentatively suggest that the Disabilities of the Arm, Shoulder and Hand, the American Shoulder and Elbow Surgeon's, and Oxford Shoulder scores may better reflect limitations in daily activities following these injuries and should be used in future studies and by clinicians.